2022
DOI: 10.1002/gch2.202200041
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land‐Use Change on the Hydrology of Lake Tana Basin, Upper Blue Nile River Basin, Ethiopia

Abstract: Human activities impact hydrology through changes in land use and land cover. This study examins the effects of changing land use on hydrological processes using the soil and water assessment tool (SWAT) model. The data is acquired from Landsat 4‐5 Thematic Mapper (TM) in 1989, Landsat 7 Enhanced Thematic Mapper Plus (ETM+) in 2005, and Landsat 8 Operational Land Inventory (OLI) in 2019. Image preprocessing, which includes georeferencing, radiometric and atmospheric correction, image enhancement, band composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Much literature published on LU conducted in the past years reported that changing natural lands to urban areas, agriculture, or bare ground will lead to frequent environmental issues and flooding due to increased runoff and peak discharge. For example, in the hydrology process (Son et al, 2022;Getachew & Manjunatha, 2022), soil quality (Vanacker et al, 2019;Padbhushan et al, 2022) and climate change (Şen, 2020); these variables are essential to the mitigation of water risk…”
Section: Methodsmentioning
confidence: 99%
“…Much literature published on LU conducted in the past years reported that changing natural lands to urban areas, agriculture, or bare ground will lead to frequent environmental issues and flooding due to increased runoff and peak discharge. For example, in the hydrology process (Son et al, 2022;Getachew & Manjunatha, 2022), soil quality (Vanacker et al, 2019;Padbhushan et al, 2022) and climate change (Şen, 2020); these variables are essential to the mitigation of water risk…”
Section: Methodsmentioning
confidence: 99%
“…The lake water quality has degraded slowly with time [15]. The explanation for this is that the amount of cultivated land in the Lake Tana area has increased by 20% and covers 68% of the basin in the last 30 years [63]. The soil erosion from these areas ranges from 5 tons per hectare per year to 50 tons per hectare per year, indicating a doubling of the sediment transport to the lake from 1980s to 2020s [64].…”
Section: Significance Of ML In Lake Water Quality Managementmentioning
confidence: 99%
“…[ 52 , 53 ] Therefore, this study is designed to use recently developed data mining methods for multispectral image classification in the BNRB. Hence, many of the previous studies [ 54 , 55 , 56 , 57 ] have employed traditional parametric statistics for the classification of multispectral imagery for land use mapping. In addition, they have applied classified satellite data to many environmental and socioeconomic applications.…”
Section: Introductionmentioning
confidence: 99%